Critical Success Factor (CSF) for Palm Plantation Land Suitability Oil Using PCA - RAHMAD ABDILLAH; SISKA KURNIA GUSTI (UIN Sultan Syarif Kasim Riau, 2018)
The importance of determining the suitability of the soil and climate will have an effect on the oil palm plant and the quality that will be produced. This study took a case study in Pelalawan district, Riau province, because Pelalawan District itself had more than 380 hectares of oil palm plantation area with 42 private companies managing it. The PCA (Principal Component Analysis) method is used to process 8 criteria consisting of temperature, rainfall, irradiation, humidity, C-Organic, pH H2O, into the soil and Slope. The data source used came from the agency that manages the land and climate of the Pelalawan districtof Riau Province. Existing data is processed and analyzed for these 8 criteria to produce determinants of success. Based on the results of research that has been done, the order of the determinants of success of oil palm planting is soil depth, rainfall, C-Organic, pH H2O, slope, irradiation, humidity and temperature.therefore, recommendations from this study will be further developed to the classification of land and climate suitability for oil palm plants.